Análisis del crowdfunding como alternativa de financiamiento para los emprendimientos en el cantón Centinela del Cóndor - Tacuri Chamba, Wilson Alfredo (2022)
The following research works presents crowdfunding as a means of fundraising and the solution for financing future entrepreneurs. The present work of curricular integration, the following research aims to analyze the crowdfunding as a viable financing for entrepreneurship. To fulfill the objectives, different types of research, methods and techniques were applied, based on an exploratory investigation and descriptive methods such as deductive and analytical techniques, as well as bibliography and survey techniques. The main findings showed that 86.15% of entrepreneurs use credit banking as the main source of financing, destined fundamentally to the maximization of its inventories, it is vital to mention that 75.81% had financing difficulties due to the lack of guarantees. Regarding the level of acceptance of the crowdfunding by entrepreneurs represents 92.31% where 75.38% would be willing to provide information on the income statement for the operations of the investor-financed projects. In this context, it was concluded that the potential entrepreneurs consider crowdfunding as a viable financing option for the development of enterprises in the canton as long as they demonstrate reliability and real benefits.